2003
DOI: 10.1002/jsfa.1540
|View full text |Cite
|
Sign up to set email alerts
|

Texture changes in fresh cut celery during refrigerated storage

Abstract: The effect of refrigerated storage temperature (0 or 10 • C) on variations in texture and lignin content of minimally processed celery was assessed. In addition, the evolution of soluble phenols was studied, as well as changes in other quality parameters, namely weight loss, surface colour and contents of chlorophyll and free sugars. To this end, celery cuts were packaged on PVC film-covered polystyrene trays. The maximum shear force required to cut the strips transversally followed a similar tendency during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
3
28
1
Order By: Relevance
“…Thus, Bolin & Huxsoll (1991), Barry‐Ryan et al. (2000) and Viña & Chaves (2003) observed increases in firmness in lettuces, sliced carrots and celery, respectively. These authors coincide in attributing the changes in texture during the storage of these vegetables to a loss of moisture (‘drying out’) together with an increase in the degree of lignification.…”
Section: Resultsmentioning
confidence: 84%
“…Thus, Bolin & Huxsoll (1991), Barry‐Ryan et al. (2000) and Viña & Chaves (2003) observed increases in firmness in lettuces, sliced carrots and celery, respectively. These authors coincide in attributing the changes in texture during the storage of these vegetables to a loss of moisture (‘drying out’) together with an increase in the degree of lignification.…”
Section: Resultsmentioning
confidence: 84%
“…In this study, it was visually observed that fresh‐cut celery displayed slight de‐green symptom accompanied by chlorophyll decrease during storage. This result was in agreement with findings of Viña & Chaves () who observed that fresh‐cut celery developed yellow colour after 7‐day storage with chlorophyll degradation. Exposing petioles to light treatment significantly alleviated such undesirable de‐green development by delaying chlorophylls degradation, indicating that light exposure was favourable to maintenance of fresh‐cut celery green colour.…”
Section: Resultsmentioning
confidence: 99%
“…Super chilling involves a partial freezing of the products, which slows down quality deterioration [4]. In [16] an experiment of celeriac stored in an refrigerated environment was carried out and various parameters were measured using traditional methods. Celeriac and carrots were the subjects of this study, where we measured the reflectance properties using a multispectral imaging device called VideometerLab which will be described in the next section.…”
Section: Introductionmentioning
confidence: 99%